2021
DOI: 10.1161/jaha.121.021861
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Myocardial Edema as Evidenced by Early Cardiac Magnetic Resonance in Survivors of Out‐of‐Hospital Cardiac Arrest: A Multicenter Study

Abstract: Background Sudden cardiac arrest (SCA) may be caused by an acute and reversible myocardial injury, a chronic and irreversible myocardial damage, or a primary ventricular arrhythmia. Cardiac magnetic resonance imaging may identify myocardial edema (ME), which denotes acute and reversible myocardial damage. We evaluated the arrhythmic outcome of SCA survivors during follow‐up and tested the prognostic role of ME. Methods and Results We included a consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Specific patterns of LGE can help determine the etiology, differentiating between ischemic, genetic or inflammatory diseases [ 49 ]. The diagnostic value of CMR in SCA survivors is well studied and repeatedly proven to be beneficial [ 19 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. The ability to identify a substrate in SCA survivors with CMR was first demonstrated by White et al, providing a diagnostic yield of 63% [ 19 ].…”
Section: The Use Of Multiple Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific patterns of LGE can help determine the etiology, differentiating between ischemic, genetic or inflammatory diseases [ 49 ]. The diagnostic value of CMR in SCA survivors is well studied and repeatedly proven to be beneficial [ 19 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. The ability to identify a substrate in SCA survivors with CMR was first demonstrated by White et al, providing a diagnostic yield of 63% [ 19 ].…”
Section: The Use Of Multiple Imaging Modalitiesmentioning
confidence: 99%
“…In contrast, findings of myocardial edema might suggest a higher survival free of arrhythmic events during follow-up, indicating the association of myocardial edema with an acute and transient arrhythmogenic substrate. However, these results need further investigation [ 51 ]. Correlating edema to specific LGE patterns will enable the differentiation between acute ischemic disease (subendocardial pattern) and acute inflammatory disease (subepicardial pattern) and might indicate the need for revascularization or additional testing with ergonovine provocation for coronary spasm [ 19 ].…”
Section: The Use Of Multiple Imaging Modalitiesmentioning
confidence: 99%
“…Yet another sequence, T2-weighted short-tau inversion recovery (T2w-STIR) has been used to assess myocardial edema in survivors of cardiac arrest. Presence of edema, hypothesized to represent a transient arrhythmogenic substrate, has been associated with fewer ICD shocks ( 61 ).…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…Zorzi et al, evaluated the impact of edema depicted on CMR in a mixed population comprising sudden cardiac arrest due to ischemic and non-ischemic cardiomyopathy. The authors found that myocardial edema was associated with a significantly higher survival free from ICD interventions (long rank: 0.04) and ICD shock (long rank: 0.03) [ 114 ]. Therefore, the authors hypothesize that myocardial edema represents only a transient arrhythmogenic substrate [ 114 ].…”
Section: Myocardial Edema and Area At Riskmentioning
confidence: 99%
“…The authors found that myocardial edema was associated with a significantly higher survival free from ICD interventions (long rank: 0.04) and ICD shock (long rank: 0.03) [ 114 ]. Therefore, the authors hypothesize that myocardial edema represents only a transient arrhythmogenic substrate [ 114 ]. Similar results were observed in a smaller cohort of patients by Zorzi et al; the authors showed that in patients who experienced out-of-hospital cardiac arrest, the presence of edema was associated with a favorable outcome [ 115 ].…”
Section: Myocardial Edema and Area At Riskmentioning
confidence: 99%